Validation of an algorithmic nutritional approach in children undergoing chemotherapy for cancer. Issue 12 (28th August 2019) - Totadri, Sidharth; Trehan, Amita; Mahajan, Diviyaa; Viani, Karina; Barr, Ronald; Ladas, Elena J.
Abstract: Background: Undernutrition impacts clinical outcome adversely in children with cancer. This study aimed to validate a nutritional algorithm with specific application to the low‐ and middle‐income country (LMIC) setting. Procedure: Fifty children with a new diagnosis of cancer were enrolled in this randomized interventional study. Weight, height/length, and mid‐upper‐arm circumference (MUAC) were measured at baseline. The study arm was administered nutritional care as per the algorithm and the control arm received the institutional standard of care. Weight was monitored regularly and MUAC was repeated after 3 months. Children were classified based on weight for height if <2 years of age or body mass index if ≥2 years, as normal, wasted, and severely wasted. The algorithmic approach comprised administration of oral supplements, nasogastric feeds, and/or parenteral nutrition based on objective assessment of the nutritional status. Results: Fifty patients were analyzed (study: 25, control: 25). Four in the study arm (16%) and six in the control arm (24%) had wasting at baseline. MUAC was <5th percentile in 15 (60%) and 13 (52%) patients in the study and control arms, respectively. At the end of 3 months, the median increment in weight was 0.8 kg (interquartile range [IQR]: –0.02; 2.00) and 0.0 kg (IQR: –0.70; 1.25) in the study and control arms, respectively ( P  = .153). The median increment in MUAC was 1.20 cm (IQR: 0.10; 2.30) and 0.00 cm (IQR: –0.50; 1.10) in the study and control arms, respectively ( P  = .020). Conclusions: The application of an algorithm designed for use in LMICs resulted in significant improvement in nutritional status, as measured by MUAC.